INDONESIA’S STRATEGY IN FACING THE POTENTIAL GLOBAL RECESSION IN 2023 - Mutthaqin, Muhammad Satrya; Adha, Raju; Tanjung, Ahmad Fuadi; Harahap, Isnaini (Proceeding International Seminar of Islamic Studies, 2023)
The world economy is expected to experience difficulties amid the threat of an imminent global recession, this is reinforced by the fact that many world central banks such as the Bank of the United States (THE FED), European Union, United Kingdom, etc. have raised their interest rates. Therefore, this is also a big concern for Indonesia. Albeit many economists say that Indonesia will survive a recession, and this opinion is supported by a report from the Central Statistics Agency (BPS) that Indonesia's economy will grow by more than 5% in 2022 despite the threat of a recession, Indonesia still needs to determine the necessary preparation strategy if a recession occurred. This study aims to analyze how Indonesia's strategy is in facing the threat of a global recession. The research method used is descriptive qualitative, using data obtained from literature studies which are analyzed in depth. The results of this study indicate that Indonesia's strategy in dealing with this threat is to increase productivity, investment and competitiveness as well as strengthen the economy and fiscal and monetary capabilities, which must also be supported by the role of the community such as business development and supporting MSME businesses in an effort to boost economic growth.